Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Wordwall Untuk Meningkatkan Kemampuan Numerasi Siswa Kelas IV Sekolah Dasar - Efitasari, Nora; Dahla, Taufiqulloh; Inggriyani, Feby (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
This study was motivated by the low numeracy skills of fourth-grade students at SDN 166 Ciateul. The study aimed to determine the improvement, impact, and extent of the impact of using the Problem-Based Learning (PBL) model supported by Wordwall media to enhance the numeracy skills of fourth-grade elementary school students. This study employed a quantitative approach using a quasi-experimental method and a Nonequivalent Control Group Design. The research sample consisted of 56 students, comprising 28 students from Class IVA as the experimental group and 28 students from Class IVB as the control group. Data collection was conducted through tests. The data were analyzed using normality tests, homogeneity tests, N-gain tests, simple linear regression tests, and effect size tests. The results of the study indicate a significant effect and improvement in numeracy skills between the experimental and control groups. The N-gain value of 78% for the experimental class indicates a high improvement, while the effect size of 3.49 falls into the large category. This indicates that the Problem-Based Learning (PBL) model supported by Wordwall has a positive effect on improving students’ numeracy skills.